Interferensi Morfologis Bahasa Melayu Betawi terhadap Bahasa Minangkabau Remaja Kota Padang - Abdurrahman, Abdurrahman; Ngusman, Ngusman; Nursaid, Nursaid (Universitas Negeri Padang, 2013)
The purpose of this research is to describtive from of interference morphology of Betawi malay language against Minangkabau languange. The aspect is (1) afiksasi, (2) reduplikasi, (3) komposisi, dan (4) akronimisasi. Methodology of research that used in this research is describtive method subject of this research is indigenous Padang city teenager total amount of Padang city teenager that made as repotrman of cardinal. According to this research result, it can comlude that ther are interference morphology Betawi malay language against Minangkabau language in Padang city teenager community. Interference morphology Betawi malay language against Minangkabau language in Padang city teenager community encompass interference to word a afiksasi and reduplikasi aspect.